207k views
0 votes
I cant figure out this problem. could really use some help

I cant figure out this problem. could really use some help-example-1

1 Answer

6 votes

There are essentially three rules in these sorts of power multiplication problems:


x^(-a) = (1)/(x^a)


x^a x^b = x^(a+ b)


(x^a)^b = x^(a b)

These rules just tell us a negative exponent means the reciprocal of the same thing with a positive exponent, that when we multiply factors with the same base we add their exponents, and when we raise something to a power to another power we get to multiply the exponents.

Let's do the algebra before we substitute (we could do it either way).


(p^2 q^(-3) )^(-2) (p^(-3)q^5)^(-2)


= (p^(-4) q^(6) ) (p^(6)q^(-10))


= p^(2) q^(-4)

Substituting p=-2, q=-1


= 2^(2) (-1)^(-4)


= 4 (1/(-1)^4) = 4\ (1/1) = 4

Answer: 4, last choice

User Kheil
by
4.3k points